Development of a Plant Based Confectionary to Combat Micro-sleepiness due to Fatigue in Hectic Life-styles and Cerebral Relaxation - Liyanage, Rumesh; Navaratne, S.B.; Wickramasinghe, Indira; Ranaweera, K.K.D.S. (Pakistan Journal of Nutrition, 2016)
Background: Micro-sleepiness (MS) is a temporary biological disorder, which can lasts from fraction of second to 30 sec and an individual fails to respond for some arbitrary sensory inputs. It has become one of the major social issues that cause fatalities, material losses, productivity and quality dilapidation and eventually negative impact on national GDP. Methodology: To combat this adverse biological phenomenon, plant based phytochemicals in berries of Piper nigrum, beans of Coffea arabica, bark of Cinnamomum verum and rhizomes of Zingiber officinale were extracted and incorporated to develop an effective confectionary. Boosting the self-confident level, mortar function, gustatory stung action, astonish olfactory and tingling actions and chemical energy were impregnated into the confection using aforesaid raw materials to combat MS. Series of confectionaries were developed based on advanced Thaguchi statistical design and best treatment was selected organoleptically against five sensory stimuli: Color, taste, mouth feel, texture, odour and overall acceptability. Results: Results revealed mean deviations of above sensory attributes were 3.85±0.81, 3.65±0.58, 3.6±0.94, 3.55±0.94, 3.45±0.76 and 3.75±0.55, respectively. Piperine, caffeine, cinnamaldehyde and gingerol were at 12.727, 5.277, 1.333 and 0.533 mg, respectively in the developed product and below the WHO standards. The developed product was capable to suppress MS completely, controlled at a satisfactory level and fails to control for 15, 65 and 15%, respectively. Further 35, 30, 20 and 15% expressed that they didn’t feel MS 1-2,